Pediatric respiratory pathogen dynamics in Southern Sichuan, China: a retrospective analysis of gender, age, and seasonal trends - Li, Qing; Song, Min; Hu, Zhi; Ding, Yinhuan; Huang, Chengliang; Liu, Jinbo (Frontiers in Pediatrics, 2024)
Objective To address the research gap in the epidemiology of pediatric respiratory tract infections (RTIs) in Luzhou, Southern Sichuan, China, by analyzing respiratory pathogens in a large pediatric cohort from 2018 to 2021, covering the pre- and during-COVID-19 periods. Methods This study conducted a retrospective analysis of children with RTIs in Luzhou from July 2018 to January 2021. Strict exclusion criteria were applied to ensure an accurate representation of the pediatric population. Pathogen detection included viruses, bacteria, and atypical agents. Results Pathogens were identified in 52.8% of 12,546 cases. Viruses accounted for 32.2% of infections, bacteria for 29.8%, and atypical agents for 29.7%, with significant findings of Staphylococcus aureus, Moraxella catarrhalis, and Mycoplasma pneumoniae. Age-related analysis indicated a higher incidence of bacterial infections in infants and viral infections in preschool-aged children, with atypical pathogens being most prevalent in 3–5-year-olds. Gender-based analysis, adjusted for age, revealed similar overall pathogen presence; however, females were more susceptible to viral infections, while males were more prone to Streptococcus pneumoniae. Notably, there was an unusual increase in pathogen cases during spring, potentially influenced by behavioral changes and public health measures related to COVID-19. Co-infections were identified as a significant risk factor for the development of pneumonia. Conclusion The study provides essential insights into the epidemiology of respiratory pathogens in pediatric populations, emphasizing the need for healthcare strategies tailored to age, gender, and seasonality. The findings highlight the impact of environmental and public health factors, including COVID-19 measures, on respiratory pathogen prevalence, underscoring the importance of targeted diagnostic and treatment protocols in pediatric respiratory infections.